GENETIC ARCHITECTURE OF INBREEDING DEPRESSION AND THE MAINTENANCE OF GAMETOPHYTIC SELF‐INCOMPATIBILITY. (1st November 2014) - Gervais, Camille; Awad, Diala Abu; Roze, Denis; Castric, Vincent; Billiard, Sylvain
Abstract: Gametophytic self‐incompatibility (GSI) is a widespread genetic system, which enables hermaphroditic plants to avoid self‐fertilization and mating with close relatives. Inbreeding depression is thought to be the major force maintaining SI; however, inbreeding depression is a dynamical variable that depends in particular on the mating system. In this article we use multilocus, individual‐based simulations to examine the coevolution of SI and inbreeding depression within finite populations. We focus on the conditions for the maintenance of SI when self‐compatible (SC) mutants are introduced in the population by recurrent mutation, and compare simulation results with predictions from an analytical model treating inbreeding depression as a fixed parameter (thereby neglecting effects of purging within the SC subpopulation). In agreement with previous models, we observe that the maintenance of SI is associated with high inbreeding depression and is facilitated by high rates of self‐pollination. Purging of deleterious mutations by SC mutants has little effect on the spread of those mutants as long as most deleterious alleles have weak fitness effects: in this case, the genetic architecture of inbreeding depression has little effect on the maintenance of SI. By contrast, purging may greatly enhance the spread of SC mutants when deleterious alleles have strong fitness effects.